Estimation of Genetic Parameters in Progenies of Terminalia arjuna (Roxb. ex DC.) Wight & Arn - Kumar, Hemant; Lal, S. B.; Wani, Afaq Majid (Indian Forester, 2019)
Efficient tree improvement strategies depend upon specific knowledge of genotypic composition of population which was visualized by their genetic parameters. The traits with high heritability along with high genetic gain is effective for further improvement programme, since they indicate the heritable additive component of variance. In context to above discussion, Terminalia arjuna a fast growing tree species having immense economic potential in various industries viz., pharmaceutical, timber, paper, soap, tannin, dye, match, food, fodder and fuel has been studied. Present study revealed significant variations between progenies (CPTs) for genotypic and phenotypic coefficient of variance, heritability, genetic gain and genetic advance. High range of variability was observed for morphological parameters viz., fresh and dry shoot/root weight, plant height, bark content and total biomass. Genotypic coefficient of variation ranged between 1.24- 44.72. However, highest GCV was recorded for fresh shoot weight (44.72 %) followed by dry shoot weight (44.49 %) while lower GCV were recorded for wood specific gravity (1.24). Heritability for different character shows significant variation (52.47-99.85). Highly heritable traits were fresh root weight (99.85), fresh shoot weight (99.80), total biomass (99.71) and plant height (98.68) while low heritability is shown by wood specific gravity (52.47). Genetic gain ranged from 1.85- 92.03 and recorded highest for fresh shoot weight (92.03%) followed by dry shoot weight (91.49 %), bark content (90.77%) and total biomass (89.10%) while lowest for wood specific gravity (1.85).